A low-complexity detection algorithm for quadrature spatial modulation systems - Kai LUO; Junwei HUANG; Pengguang ZHOU; Hao XU; Can WU (Dianxin kexue)
To tackle the issues of the uncertainty number of the activated antennas and high computational complexity of maximum likelihood (ML) detection algorithm in quadrature spatial modulation (QSM),a low-complexity detec-tion algorithm was proposed.Firstly,the system model was reconstructed into a new model suitable for low-complexity detection algorithms in fixed active antennas systems based on compressed sensing (CS) signal re-construction theory.Then,based on the idea of orthogonal matching pursuit (OMP) algorithm and reconstructed model,a candidate set of activated antennas was obtained.Lastly,using ML algorithm to search the candidate,the index of activated antennas and the modulation symbol were selected.Simulation results show that the proposed de-tector is capable of achieving about 90% reduction in complexity with low performance loss compared with ML al-gorithm.